The specialized pro-resolving lipid mediator Protectin D1 affects macrophages differentiation and activity in Adult-onset Still’s disease and COVID-19, two hyperinflammatory diseases sharing similar transcriptomic profiles - Navarini, Luca; Vomero, Marta; Currado, Damiano; Berardicurti, Onorina; Biaggi, Alice; Marino, Annalisa; Bearzi, Pietro; Corberi, Erika; Rigon, Amelia; Arcarese, Luisa; Leuti, Alessandro; Fava, Marina; et al. (Frontiers in Immunology, 2023)
Introduction: COVID-19 and autoinflammatory diseases, such as Adult-onset Still’s Disease (AOSD), are characterized by hyperinflammation, characterized by massive production, and uncontrolled secretion of pro-inflammatory cytokines. The specialized pro-resolving lipid mediators (SPMs) family is one the most important processes counteracting hyperinflammation inducing tissue repair and homeostasis restoration. Among SPMs, Protectin D1 is able to exert antiviral features, at least in animal models. The aim of this study was to compare the transcriptome of peripheral blood mononuclear cells (PBMCs) from patients with AOSD and COVID-19 and to evaluate the role of PD1 on those diseases, especially in modulating macrophages polarization. Methods: This study enrolled patients with AOSD, COVID-19, and healthy donors (HD), undergoing clinical assessment and blood sample collection. Next-generation deep sequencing was performed to identify differences in PBMCs transcripts profiles. Plasma levels of PD1 were assessed by commercial ELISA kits. Monocyte-derived macrophages were polarized into M1 and M2 phenotypes. We analyzed the effect of PD1 on macrophages differentiation. At 10 days, macrophages were analyzed for surface expression of subtypes markers by flow cytometry. Cytokines production was measured in supernatants by Bio-Plex Assays. Results: In the transcriptomes from AOSD patients and COVID-19 patients, genes involved in inflammation, lipid catabolism, and monocytes activation were specifically dysregulated in AOSD and COVID-19 patients when compared to HDs. Patients affected by COVID-19, hospitalized in intensive care unit (ICU), showed higher levels of PD1 when compared to not-ICU hospitalized patients and HDs (ICU COVID-19 vs not-ICU COVID-19, p= 0.02; HDs vs ICU COVID-19, p= 0.0006). PD1 levels were increased in AOSD patients with SS ≥1 compared to patients with SS=0 (p=0.028) and HD (p=0.048). In vitro treatment with PD1 of monocytes-derived macrophages from AOSD and COVID-19 patients induced a significant increase of M2 polarization vs control (p<0.05). Furthermore, a significant release of IL-10 and CCL4 from M2 macrophages was observed when compared to controls (p<0.05). Discussion: PD1 is able to induce pro-resolutory programs in both AOSD and COVID-19 increasing M2 polarization and inducing their activity. In particular, PD1-treated M2 macrophages from AOSD and COVID-19 patients increased the production of IL-10 and enhanced homeostatic restoration through MIP-1β production.